2014
DOI: 10.1111/acem.12506
|View full text |Cite
|
Sign up to set email alerts
|

Association Between the Seat Belt Sign and Intra‐abdominal Injuries in Children With Blunt Torso Trauma in Motor Vehicle Collisions

Abstract: Objectives: The objective was to determine the association between the abdominal seat belt sign and intra-abdominal injuries (IAIs) in children presenting to emergency departments with blunt torso trauma after motor vehicle collisions (MVCs).Methods: This was a planned subgroup analysis of prospective data from a multicenter cohort study of children with blunt torso trauma after MVCs. Patient history and physical examination findings were documented before abdominal computed tomography (CT) or laparotomy. Seat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…As the coexistence of a seat-belt sign and abdominal pain is associated with an increased risk of intraabdominal injuries [17] and considering the high mortality rates of TBR, ranging from 11% to 22% [4] , [18] , an immediate and adequate diagnostic approach followed by an appropriate therapy is indicated, while physicians should maintain a high level of suspicion for urologic injuries following blunt abdominal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…As the coexistence of a seat-belt sign and abdominal pain is associated with an increased risk of intraabdominal injuries [17] and considering the high mortality rates of TBR, ranging from 11% to 22% [4] , [18] , an immediate and adequate diagnostic approach followed by an appropriate therapy is indicated, while physicians should maintain a high level of suspicion for urologic injuries following blunt abdominal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of abdominal skin bruising may be indicative for visceral organ injuries. Several studies have pointed out, that bruising in a seat belt pattern was associated with intra-abdominal injury in 20-60% of cases [6]. The risk of perforated bowel injury increased by a 2.4 factor whenever seat belt bruising was detected [7].…”
Section: Case Presentationmentioning
confidence: 99%
“…A planned sub-analysis of a prospective study of 12,000 children with blunt torso trauma had shown a greater risk for intra-abdominal injuries in patients with a seat belt sign than in those without a seat belt sign (relative risk, 1.6), and was largely indicative of an increased risk for gastrointestinal injuries (RR, 9.4). Children with seat belt signs had an increased risk for undergoing any acute interventions (RR, 4.5), including therapeutic laparotomy (RR, 9.5) [3]. Some evidences had shown a similar trend among the adult population.…”
Section: Introductionmentioning
confidence: 97%